Eksistensi Sineas Perempuan dalam Ekosistem Perfilman di Bandung - Rembulan, Dara Bunga; Swaradesy, Rufus Goang (Mudra Jurnal Seni Budaya, 2024)
The art of filmmaking is a creative process that involves collaboration from various parties and aspects. This also inspired women filmmakers to create their own works. Many women filmmakers have successfully addressed important issues through their films. The number of women filmmakers in Bandung is still relatively low. Based on data obtained from film communities in Bandung, women filmmakers account for only about one-third of the total number. However, women filmmakers have achieved various notable accomplishments on both national and international levels. This research was conducted to understand the presence of women filmmakers in Bandung within the scope of the national film. Data were obtained in collaboration with Bandung Film Commission (BFC). The informants were women filmmakers who are originally from Bandung and have made contributions to the national film industry. This paper represents a qualitative descriptive study. The research subjects were women filmmakers in Bandung, and the selection of informants was done using purposive sampling techniques. The results of the research indicate that the presence of women filmmakers does not happen instantly. There are internal and external factors that support the development of skills in filmmaking. The level of filmmaking activity in the region is crucial, making the presence of film communities in Bandung highly supportive of the emergence of women filmmakers on the national stage. The existence of women filmmakers is marked by their works, attitudes, and professions. To sustain the existence of women filmmakers, harmony between the realms of education, the professional world, and film associations is essential.